VD_FINDINFO Jug / 2012 / 175 vom 11. Oktober 2012 - VD Tribunal cantonal (2012)
CONTRAT D'OUVERTURE DE CRÉDIT, COMPTE COURANT, RECONNAISSANCE DE DETTE, NOVATION, SOLIDARITÉ, INTERPRÉTATIONSENS GÉNÉRAL | 102 al. 1 CO, 117 al. 2 CO, 117 al. 3 CO, 143 CO, 18 CO, 20 CO, 79 al. 1 LP